Clindamycin as unique antibiotic choice in Hidradenitis Suppurativa. Issue 2 (21st December 2018) - Rosi, Elia; Pescitelli, Leonardo; Ricceri, Federica; Di Cesare, Antonella; Novelli, Andrea; Pimpinelli, Nicola; Prignano, Francesca
Abstract: The rifampicin (RF)–clindamycin (CL) combination is recommended as first line therapy in moderate to severe Hidradenitis Suppurativa (HS) by European S1 guidelines. Although prolonged use of RF should be discouraged, there are currently few alternatives to this combination therapy. The aim of the present study was to assess retrospectively the efficacy of oral CL monotherapy in patients diagnosed with HS. In the period January 2017–May 2018, 31 HS patients who received a 300 mg b.i.d. oral dose of CL were studied retrospectively. Efficacy of the treatment was evaluated by comparing the main HS severity scores (Sartorius score modified by Revuz, Hidradenitis Suppurativa Physician Global Assessment [HS‐PGA] and International Hidradenitis Suppurativa Severity Score System [IHS4]) before (W0) and after (W12) CL oral therapy. CL efficacy was demonstrated by the extreme and significant reduction of all three disease severity parameters during the 12‐week period ( p ≤ .01). There was also a statistically significant change in the mean visual analogue scale for pain. The present study demonstrates the efficacy of oral CL monotherapy as RF‐sparing regimen alternative to RF–CL combination in a selected group of patients.